Significance of Extra Hepatic Portal Vein Variations in Hepatopancreatic Surgeries - Kanasker, Neelesh; Sonje, Preeti; Bankar, Janhavi; Vatsalaswamy, . (Highlights on Medicine and Medical Science Vol. 3, 2021)
Introduction: Knowing the variations in the portal vein's path is important when performing pancreas and duodenum surgeries. It is also useful in the treatment of traumatic mesentery rupture. In surgical resection and transplantation, Awareness about the variations of the portal vein is vital, especially during pre-treatment planning, to lower the complication rates of the surgical and radiological treatments. Furthermore, a thorough understanding of portal vein variations is critical in assessing the technical feasibility of surgical interventions such as liver transplantation, portal vein embolization prior to hepatectomy, and postoperative care. Aim: The goal of this study is to look at the anatomical variations of the portal vein, correlate the findings with clinical problems, and provide a good ontological explanation. Materials and Methods: In this study, Twenty four cadavers embalmed in 10% formalin were procured from the department of anatomy and were dissected. Variations were cleaned and photographed with great care. Results: The creation of the portal vein by the confluence of the superior mesenteric, inferior mesenteric, and splenic veins (1 case), as well as the inferior mesenteric vein terminating in the superior mesenteric vein (6 cases), were among the variations observed. Conclusion: This research was undertaken with the intention of determining the approximate percentage of incidence of major variations in the formation of portal vein. Preventing severe intraoperative haemorrhage can thus be avoided by being aware of such variations before the major abdominal procedures.